Using a Generalized Differenced Demand Model to Estimate Price and Expenditure Elasticities for Milk and Meat in Austria - Andreas Widenhorn; Klaus Salhofer (German Journal of Agricultural Economics (GJAE), 2014)
Applying a generalized demand system approach, we estimate both current price and expenditure elasticities in the Austrian food retail market based on a dataset covering a time period of approximately ten years. Within the framework of a three-stage-budgeting approach, more disaggregated demand reactions for milk products and types of meat are estimated. Conformable with demand theory, price reactions are found to be less elastic the more aggregated the product groups are. Generally, demand for pork and beef turns out fairly price-elastic. Similarly, price reactions for cheese and milk are stronger than average estimates for European markets. Substitution patterns are more distinct than those found in a comparable study for Germany. In addition, our study indicates the importance of modeling a comprehensive budgeting process rather than isolated levels of product aggregation when deriving both price and expenditure elasticities of demand.
Keywords: 330; Milch; Fleisch; Preiselastizität; Einkommenselastizität der Nachfrage; Österreich